Evaluation Of Health Services Regional Public Hospital Besemah in Pagar Alam City of South Sumatra - . Yuslainiwati; Budiman Rusli; Josy Adiwisastra; Sinta Ningrum (Bandar Lampung University, 2015)
Hospital (Hospital) Besemah Pagar Alam is the property of the City of Pagar Alam in organizing the service is often a gap between perceived service with the services provided at the hospital. Problems that occur in hospitals BesemahPagar Alam is the number of medical personnel, infrastructure, information and communication systems less. This study aimed to evaluate health care in hospitals BesemahPagar Alam is then expected to acquire a new concept for the development of Public Administration. This study used a qualitative approach. Collecting data using literature study, observation and interviews, Focus Group discutions and study documents. The survey results revealed that the quality of health care at the Regional Hospital Besemah Pagar Alam city seen from the dimensions of service quality dimensions tangibless seen less and Responsiveness enough. Equip assessment results Model of The Australian Council on Health Care Standards (Achs) achievement rating Some few then obtain Achievement (SA), the level of achievement Hospital Accreditation Standards are lacking.